PARTISIPASI PEMILIH PEMULA PADA PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA DUMAI TAHUN 2015 - Randy Helnal Dinata; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Political participation in a democracy is an indicator of the implementation of the organization of the powers of the highest state legitimate by the people (popular sovereignty), which is manifested individual's involvement in the democratic party (Elections). The higher the level of political participation indicates that people follow and understand and get involved in state activities. Judging from the comparison of voters who voted in the local elections in Kota Dumai increased participation of voters, namely 1.40% in 2010 to rise to 2.34% in 2015, meaning that there is an increasing participation of voters of 0.94% or as many as 1,680 people. These circumstances attractive for their positive participation of voters towards elections is an event important for the political education of students.The purpose of this study was to determine to analyze the causes of the increase in the participation of voters in the election of Mayor and Deputy Mayor of Dumai 2015 and to analyze the efforts made General Election Commission (KPU) Dumai to increase the participation of voters in the election of Mayor and Deputy Mayor Dumai Year 2015. in this study, the concept used refers to the theory Paige. This study used a descriptive approach. For sample use sampling techniques purvosive. Data collection techniques used were questionnaires, interviews and documentation. Quantitative analysis along with the data quality of a percentage (%).The results of this study can be concluded that the level of participation of voters in the election of Mayor and Deputy Mayor of Dumai 2015 is Active Participation, the cause of the increase in the participation rate of voters because the Commission managed to motivate voters to participate in the Election of Mayor and Deputy Mayor of Pekanbaru 2015, thus contributing sound enough voters to support the government in accordance with the purpose of elections to be achieved in Dumai. Efforts to socialize the implementation of Election of Mayor and Deputy Mayor of Dumai already done optimally. Because the Commission has been put up billboards socialization in each sub-district office and district office, in the center of the crowd and socialization to school.Keywords: Participation, Voter Starter